KEBERADAAN DAN BENTUK TRANSFORMASI CERITA PANJI - Ida Bagus Manuaba (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe the existence, values, and art forms inspired by Panji stories. The data sources were Panji stories and art forms as results of Panji story reception. The data were collected through documentation, recording, and observations. They were analyzed using a qualitative textual method with a literary reception perspective. The findings are as follows. First, Panji stories are resources for the development of arts and cultures spreading widely and acknowledged as Panji cultures. Second, there are ten values in Panji stories, i.e. history, education, exemplary deeds, heroism, culture, aesthetics, local wisdom, ecology, politics, and morality. Third, art and cultural forms inspired by Panji stories include literary works (folklores/classical literature), temple reliefs, dances, performances, and paintings.